Nutrient (N,P) dynamics, hydrology, and sedimentation rates of Lake Neshonoc, La Crosse, Wisconsin - Ritter, Paul Gerard (My University, 1986)
Lake Neshonoc is a reservoir (243 ha) on the La Crosse River in the Driftless Area of southwestern Wisconsin. Water sample were collected from the four influent waters (Adam's Valley Creek, Burn's Creek, Dutch Creek, and the La Crosse River), the marsh upstream from the lake, four sites within the lake, and one site downstream from the dam. Two deep water sites in the lake were sampled at the surface, middle, and near-bottom of the water column. Samples were collected from all sites from February through September, 1985, at which time the lake was drained for dam repairs. Influent samples were collected through December, 1985. Temperature, dissolved oxygen, and Secchi disk transparency were recorded in the field. Non-filterable residues, specific conductance, pH, total alkalinity, nitrate, nitrite, ammonia, ortho-phosporus, and total phosporus were analyzed in the laboratory. Total alkalinity, pH, and conductivity were typical of a well-buffered lake. Dissolved oxygen in the lake fluctuated from top to bottom on a biweekly basis during the summer. Of the influent waters, Adam's Valley Creek consistently had the highest concentrations of nutrients. Within the lake, nitrate and ortho-phosphorus concentrations decreased 35% from the inflow sites to the outflow site. This was likely due to assimilation by phtyoplankton, which may have increased the biological oxygen demand and decreased the dissolved oxygen in the deeper waters (3 m) of the lake. The La Crosse River supplies a majority of the water entering Lake Neshonoc, which explains the similarity between the lake and river water chemistry. The lake has lost 73 ha in the past 29 years. 23% of its original surface area. Most of the loss occurred with the encroachment of the marsh. The lake volume has decreased O.42x106m3 during the past 19 years. Hydraulic residence time for Lake Neshonoc is 4.85 days. Improvements in watershed management must be implemented to prolong the benefits of this reservoir.
Keywords: Ecological surveys -- Wisconsin -- Lake Neshonoc; Ecology -- Wisconsin -- Lake Neshonoc; Neshonoc, Lake (Wis.)